Optimisation of Enzyme-Assisted Extraction of Oil Rich in Carotenoids from Gac Fruit (Momordica cochinchinensis Spreng.) - Huỳnh Cang Mai; Vĩnh Tru'o'ng; Frédéric Debaste (Food Technology and Biotechnology, 2013)
Gac (Momordica cochinchinensis Spreng.) fruit arils contain an oil rich in carotenoids, especially lycopene and β-carotene, which can be enzymatically extracted in water. Response surface methodology was used to determine the factors influencing the enzymatic extraction of oil from gac fruit arils. A central composite design with four independent variables, namely enzyme mass per volume ratio, time, temperature and the stirring speed of the reaction, was carried out. The results show that all of these four factors have a significant effect on the oil yield recovery, with no significant interaction between these factors. Under the optimum conditions obtained (enzyme mass per volume ratio of 14.6 %, incubation time of 127 min, temperature of 58 °C and stirring speed of 162 rpm), it is estimated that the maximum oil recovery and the total carotenoid extraction per dry mass would be 79.5 % and 5.3 mg/g, respectively. There is a strong correlation between the oil recovery and total carotenoid content. The physicochemical properties of the extracted gac oil were characterised. Finally, the Schaal oven test shows that conservation time of gac oil is comparable to that of other edible oils.